Bioinformatics, Molecular Docking and Experiments In Vitro Analyze the Prognostic Value of CXC Chemokines in Breast Cancer - Wang, Fei; Yuan, Chong; Wu, He-Zhen; Liu, Bo; Yang, Yan-Fang (Frontiers in Oncology, 2021)
The increasing incidence and mortality rate of Breast cancer (BC) make it a major public health problem around the world. CXC chemokines can mediate the migration of immune cells and regulate apoptosis in tumor. However, the expression and prognostic value of them in BC and their targeted drugs have not been clarified. Therefore, in this study, ONCOMINE, GEPIA2.0, UALCAN, Venny2.1.0, cBioPortal, STRING, Gene MANIA, Pathway Commons, DAVID6.8, Omicshare, Cytoscape3.6.1, TIMER2.0, Drug Bank, TCMSP, RSCBPDB, PubChem, pkCSM, Chem Draw, AutoDockTools-1.5.6 and PyMOL were utilized for analysis. The expression of CXCL1-3, CXCL9-13 between BC and normal tissues was significantly different in all the three databases. And the expression of CXCL1-2, CXCL12-13 was correlated with the stages of BC. But only CXCL1-3 were prone to mutation, and negatively correlated with survival and prognosis of BC patients. Taken together, CXCL1-2 might be therapeutic targets and biomarkers for BC patients. In addition, both of them were associated with immune infiltration. The results of molecular docking showed that Quercetin was most likely to be developed as drugs that interacted directly with CXCL1-2. And GLU29 of CXCL1, ASP-1, PRO-96, TRP-47 and LEU-45 of CXCL2 were the most potential sites, which provided valuable reference for further study of pharmacodynamics and mechanism. In addition, the inhibitory effect of Quercetin on proliferation and promoting apoptosis of BC related cell lines were confirmed in vitro. Western blot and Real-Time PCR confirmed that it increased the expression of CXCL1-2 in MDA-MB-231 and MCF-7 cells.